Monitoring and information system structure. - Mustapha, Mazlina
The purpose of this paper is to investigate how the information system structure of an organisation affects its demand and preference for monitoring costs in Malaysian business environment. Data is collected using primary source. Multiple regression analysis is used. The findings indicate that companies using centralised information system structure have negative and significant relationship with total monitoring costs. However the information system structure is not significant when the cost of directorship and auditing are compared. But when internal auditing and external auditing costs are compared, the result indicates that companies with centralised information system structure have significantly more internal auditing costs.